The myelination puzzle: do fibroblast growth factors and their receptors have regulatory roles in peripheral nerve myelination? - Dağlıkoca, Emine Duygu. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2014., 2014)
Axon-Schwann cell interaction is the key step in myelination and critical in the pathogenesis of peripheral neuropathies. Molecules mediating this interaction to promote the complex mechanism of myelination have not been elucidated properly yet. However, recent studies emphasized the importance of tyrosine kinase receptor signaling in the process. Although expression of FGFs and their tyrosine kinase receptors FGFRs have been shown in PNS, little information is available about their regulation during the myelination process. In this study, we aimed to investigate whether FGF1, FGF2, FGF9 that were previously implicated in CNS development, involved in peripheral nerve myelination and regulate axon-Schwann cell interactions, through their high affinity receptors FGFR1-3. For this purpose, we used dorsal root ganglia (DRG) and the sciatic nerve from mice as in vivo models and Schwann cell-neuron co-culture developed from fetal mouse DRG tissue as an in vitro model. The expression patterns and localization of the molecules were investigated both in vivo and in vitro. Among the three FGFs analysed, FGF1 was chosen as a candidate for further investigation because of its high level of expression in all tested tissue types with an axonal localization. In contrast, FGFR1-3 were found to be expressed by Schwann cells. Protein expression levels of FGF1 and FGFR1-3 were examined through the developmental stage to adulthood from sciatic nerves by Western blotting. Both FGF1 and its receptors were found to be modulated at key time points of the myelination route. Immunolabeling studies showed that FGF1 expression in neurons and FGFR1-3 expression in Schwann cells continued throughout the process. When FGF1 was blocked in DRG culture, a reduction in the levels of myelin proteins and in the number of myelinated axonal segments was observed. Our findings provide evidence for the first time for the involvement of FGF1 in peripheral nerve myelination and suggest that FGF1 signaling through FGFR1-3 have regulatory roles at the onset of myelination, in myelin compaction and protection of the stability of mature structure.
Keywords: Myelination.; Neuroglia -- Growth -- Molecular aspects.